Training on the Utilisation of Backyards through the Planting of Chili, Eggplant, and Tomatoes with the Aisyiyah Durungbedug Branch Leaders to Support Food Security and the Achievement of the SDGs: Pelatihan Pemanfaatan Pekarangan Melalui Penanaman Cabai, Terong, dan Tomat Bersama Pimpinan Ranting Aisyiyah Durungbedug Untuk Mendukung Ketahanan Pangan dan Pencapaian SDGs - Abror, M.; Miftakhurrohmat, A.; Prihatiningrum, Andriani Eko; Rachmadani, Putri Karina; Rabbani, Abdullah Fahmi; Septabrina, Canda Kharisma (Universitas Muhammadiyah Sidoarjo, 2025)
Food security is a strategic issue that needs to be addressed through a local and participatory approach. Durungbedug Village, Candi District, Sidoarjo Regency has the potential for yard land that has not been utilized optimally. Through a community service program involving Aisyiyah Branch Leaders, this activity aims to empower the community, especially women, in managing yards into productive land based on horticultural cultivation (chili, eggplant, and tomato). The implementation method includes training, technical assistance, application of simple technology, and evaluation of results. The results of the activity showed an increase in participants' skills in cultivation, yard utilization, and contribution to household income. This program has a positive impact on the achievement of the SDGs, especially the goals of SDG 2 (No Hunger) through the provision of sustainable food, SDG 12 (Responsible Consumption and Production) by encouraging environmentally friendly agricultural practices, and SDG 15 (Terrestrial Ecosystems). Highlights: Empowers women through horticultural training and yard optimization. Increases household income and food availability at the local level. Supports SDGs 2, 12, and 15 with sustainable, eco-friendly practices. Keywords: yard, food security, Aisyiyah, horticulture, community service